Bacterial contamination of computer touch screens. - Gerba, Charles P.; Wuollet, Adam L.; Raisanen, Peter; Lopez, Gerardo U. (American Journal of Infection Control, 2016)
The goal of this study was to determine the occurrence of opportunistic bacterial pathogens on the surfaces of computer touch screens used in hospitals and grocery stores. Opportunistic pathogenic bacteria were isolated on touch screens in hospitals; Clostridium difficile and vancomycin-resistant Enterococcus and in grocery stores; methicillin-resistant Staphylococcus aureus . Enteric bacteria were more common on grocery store touch screens than on hospital computer touch screens.